Complementation of the Magnaporthe grisea cpkA mutation by the Blumeria graminis PKA-c gene: functional genetic analysis of an obligate plant pathogen - Bindslev, L.; Kershaw, M.; Talbot, N.; Oliver, Richard (2001)
Obligate plant-pathogenic fungi have proved extremely difficult to characterize with molecular genetics because they cannot be cultured away from host plants and only can be manipulated experimentally in limited circumstances. Previously, in order to characterize signal transduction processes during infection-related development of the powdery mildew fungus Blumeria graminis (syn. Erysiphe graminis) f. sp. hordei, we described a gene similar to the catalytic subunit of cyclic AMP-dependent protein kinase A (here renamed Bka1). Functional characterization of this gene has been achieved by expression in a ΔcpkA mutant of the nonobligate pathogen Magnaporthe grisea. This nonpathogenic M. grisea ΔcpkA mutant displays delayed and incomplete appressorium development, suggesting a role for PKA-c in the signal transduction processes that control the maturation of infection cells. Transformation of the ΔcpkA mutant with the mildew Bka1 open reading frame, controlled by the M. grisea MPG1 promoter, restored pathogenicity and appressorium maturation kinetics. The results provide, to our knowledge, the first functional genetic analysis of pathogenicity in an obligate pathogen and highlight the remarkable conservation of signaling components regulating infection-related development in pathogenic fungi.